2018
DOI: 10.31219/osf.io/szvtq
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Adult Mortality Differentials and Regional Development at the local level in Brazil, 1980-2010

Abstract: In this paper, we study study spatial and temporal adult mortality trends in small areas of Brazil, from 1980 to 2010, and its relation to socioeconomic and public health developments. Brazil is marked by huge regional and social inequality and it is important to understand how it could be related to trends and differences in adult mortality. There are several studies about trends in infant and child mortality, but much less is known about adult mortality. We are also interested in understand whether there is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 18 publications
(28 reference statements)
1
3
0
Order By: Relevance
“…Unemployment was the variable with the second most predictive power, which validates the vast literature documenting the strong associations between disadvantage in the job market and both health and mortality (Iversen et al 1987;Moser et al 1987;Roelfs et al 2011, Queiroz et al 2017. High unemployment rates are related to low growth and economic development.…”
Section: Discussionsupporting
confidence: 77%
See 3 more Smart Citations
“…Unemployment was the variable with the second most predictive power, which validates the vast literature documenting the strong associations between disadvantage in the job market and both health and mortality (Iversen et al 1987;Moser et al 1987;Roelfs et al 2011, Queiroz et al 2017. High unemployment rates are related to low growth and economic development.…”
Section: Discussionsupporting
confidence: 77%
“…In contrast, employment has been associated with positive characteristics, such as greater self-esteem and independence. Queiroz et al (2017) found that high levels of unemployment were associated with a greater probability of adult deaths in Brazil. In a longitudinal study conducted in Sweden, Montgomery et al (2013) found that among men aged 34 to 38 years and those aged 45 to 49 years, the risk mortality related to unemployment is greater in the older group and among more qualified individuals.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations